Design Tools for Bolted End-Plate Beam-to-Column Joints - Giusy Terracciano; Gaetano Della Corte; Gianmaria Di Lorenzo; Raffaele Landolfo (Journal of Engineering)
Predicting the response of beam-to-column joints is essential to evaluate the response of moment frames. The well-known component method is based on a mechanical modelling of the joint, through joint subdivision into more elementary components subsequently reassembled together to obtain the whole joint characteristics. Significant advantages of the component method are the following: (i) the mechanics-based modelling approach; (ii) the easier general characteristics of components. However, the method is commonly perceived by practicing engineers as being too laborious for practical applications. Within this context, this paper summarizes the results of a theoretical study aiming to develop simplified analysis tools for bolted end-plate beam-to-column joints, based on the Eurocode 3 component method. The accuracy of the component method was first evaluated, by comparing theoretical predictions of the plastic resistance and initial stiffness with corresponding experimental data collected from the available literature. Subsequently, design/analysis charts were developed through a parametric application of the component method by means of automatic calculation tools. They are easy and quick tools to be used in the first phases of the design process, in order to identify joint configurations and geometrical properties satisfying specified joint structural performances. The parametric analysis allowed also identifying further simplified analytical tools, in the form of nondimensional equations for predicting quickly the joint structural properties. With reference to selected geometries, the approximate equations were verified to provide sufficiently accurate predictions of both the stiffness and the resistance of the examined beam-to-column joints.